Accelerated formation of the boron–oxygen complex in p‐type Czochralski silicon. Issue 5 (2nd April 2015) - Hamer, Phillip; Hallam, Brett; Abbott, Malcolm; Wenham, Stuart
<x xml:space="preserve">Abstract</x> This Letter reports on the acceleration of the rate of formation of the boron–oxygen defect in p‐type Czochralski silicon with illumination intensities in excess of 2.1 × 1017 photons/cm2/s. It is observed that increased light intensities greatly enhance the rate of defect formation, without increasing the saturation concentration of the defect. These results suggest a dependence of the defect formation rate upon the total majority carrier concentration. Finally, a method using temperatures up to 475 K and an illumination intensity of 1.68 × 1019 photons/cm2/s is shown to result in near‐complete defect formation within seconds. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)